2021
DOI: 10.1177/0091217421989144
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities and quality of life in breast cancer patients undergoing radiation treatment: Risk and protective factors

Abstract: Objective The primary goal was to evaluate the prevalence of psychiatric comorbidities and changes in psychological distress levels among breast cancer patients receiving radiotherapy (RT). The secondary goal was to determine risk and protective factors for psychiatric comorbidities of these patients. Methods From June 2018 to November 2019, patients were recruited from the hospital, Department of Psychiatry. Patients completed baseline surveys after seeing their radiation oncologist and prior to the first tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Assessment of QoL among cancer patients is imperative, as a patient’s mood and self-perception can negatively affect the results of treatment (29–31). Researchers have suggested that cancer patients with higher levels of positivity and support tend to follow medical treatment and report fewer negative symptoms and use of coping strategies against the challenges of illness ( 29 31 ). Patients with gynecologic malignancies, especially cervical cancer, show high prevalence of psychiatric symptoms ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of QoL among cancer patients is imperative, as a patient’s mood and self-perception can negatively affect the results of treatment (29–31). Researchers have suggested that cancer patients with higher levels of positivity and support tend to follow medical treatment and report fewer negative symptoms and use of coping strategies against the challenges of illness ( 29 31 ). Patients with gynecologic malignancies, especially cervical cancer, show high prevalence of psychiatric symptoms ( 32 ).…”
Section: Discussionmentioning
confidence: 99%